2021
DOI: 10.1007/s12649-021-01486-y
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Agricultural Digestate for the Ammonium Sulfate Recovery and Soil Improvers Production

Abstract: This work investigates an innovative process to valorise agricultural digestate by the exploitation of solar energy. Digestate has been located in a lab-scale greenhouse to evaporate the liquid phase. Digestate vapours, rich in ammonia, are sent in a Drechsler trap, filled with 38% w/w sulfuric acid solution, through three solar air fans. A concentration of about 2 M of ammonium sulphate solution was recovered. The remaining dried solid phase, rich in phosphorous compounds, was evaluated as alternative to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…
Fig. 9 a The Nijhuis Ammonium Recovery System (amended and redrawn after [ 201 ]); b recovery of nitrogen as ammonium sulfate from the ADDC (conceptualized from [ 202 ])
…”
Section: Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…
Fig. 9 a The Nijhuis Ammonium Recovery System (amended and redrawn after [ 201 ]); b recovery of nitrogen as ammonium sulfate from the ADDC (conceptualized from [ 202 ])
…”
Section: Solutionsmentioning
confidence: 99%
“…Nitrogen recovery using chemical stripping is an energy-extensive process with high temperature and chemical treatments (NaOH and H 2 SO 4 ) [ 202 ]. Battista et al [ 202 ] in an innovative step performed recovery of nitrogen as ammonium sulfate (~2M, yield under optimized process) from ADDC using solar energy-driven lab-scale greenhouse (Fig. 9b ).…”
Section: Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen and phosphorus recovery from LF is also practiced through struvite precipitation and ammonia stripping [15]. Although many authors confirmed a high fertilizer value of struvite and ammonium sulphate [16][17][18], the recovery methods have limited practical application. This results from the fact that the alkaline effluent remaining after these processes is characterized by considerable salinity.…”
Section: Introductionmentioning
confidence: 99%